PE N GA RU H PE MU PU KA N B O KASH I E CE N G GO N DO K D AN PU PU K ORGANIK CAIR AZOLLA TERHADAP KADAR C-ORGANIK, N-TOTAL TANAH DAN SERAPAN HARA NITROGEN TANAMAN KEDELAI (Glycine max (L.) Merill.) PADA TANAH PASIRAN - Kartika Sholehatin; Tri Candra Setiawati (Berkala Ilmiah Pertanian, 2020)
Sandy soil has low productivity; it takes some efforts to gain the quality of sandy soil by giving organic material. The organic materials that can be used are Bokashi water hyacinth and Azolla liquid organic fertilizer. The aim of this study is to know the effect of Bokashi water hyacinth fertilization and Azolla liquid organic fertilizer on the uptake of N element and the growth of soybean plant in sandy soil. This study uses Complete Random Design (CRD) which consists 9 combinations, i.e. B0 (Control), B1 (0g N Bokashi and 0.5g N POC), B2 (0g N Bokashi and 0.4g N POC), B3 (0.1g N Bokashi and 0.4g N POC, B4 (0.2g N Bokashi and 0.3g N POC), B5 (0.3g N Bokashi and 0.2g N POC), B6 (0.4g N Bokashi and 0.1g N POC), B7 (0.4g N Bokashi and 0g N POC) and B8 (0.5g N Bokashi and 0g N POC). The combination of 11,45 gr water hyacinth is equal to 0,3 % N 30 ml and Azolla POC is equal to 0,2 % N on soybean plant which absorbs the highest N and has the highest amount of effective nodules. The nutrient availability is related to nutrient composition which is available in the ground and can be absorbed by plants. Keywords: Sandy Soil, Bokashi, Hyacinth, Liquid Organik Fertilizer, Azolla, Soybean